VD_FINDINFO HC / 2013 / 36 vom 5. Dezember 2012 - VD Tribunal cantonal (2012)
ASSISTANCE JUDICIAIRE, SOCIÉTÉ ANONYME, PERSONNE MORALE | 117 CPC (CH), 121 CPC (CH), 319 let. b ch. 1 CPC (CH), 322 al. 1 CPC (CH)